Histopathological Grading and Enzyme Histochemical Study of the Placenta in Gestational Diabetes Mellitus Pregnant Women (Medico Legal Update, 2020)
Gestational diabetes mellitus (GDM) constitutes carbohydrate metabolism disorders that lead to severe andsometimes life-threatening complications of pregnancy.Materials and Method: 40 placenta biopsies with blood samples were taken from gestational diabeticpregnant women and 20 placenta biopsies with blood samples were taken from healthy pregnant women,the tissues were fixed, processed, embedded and cutting separately depending on procedure for enzymehistochemical and routine histological technique and the blood was centrifuged.Results: The histological changes in the GDM group represented by villous oedema in approximately (30%)of the GDM group, an excessive amount of collagen fibres in the villous stroma (57.5%). Syncytial knotswere formed (70 %) in addition to an excessive number of cytotrophoblast cells in about (65 %). The stromalfibrinoid deposition was noticed in (52.5 %). Hypo-vascular villi are seen in (32.5%) also, atherosis of theuteroplacental arteries in (40%) of biopsies. In enzyme histochemistry, the villous stroma of the GDM grouphas a strong reaction to the G-6-P enzyme. There is a significant increase (p